2010
DOI: 10.1002/cncr.24945
|View full text |Cite
|
Sign up to set email alerts
|

Reduced incidence of infusion‐related reactions in metastatic colorectal cancer during treatment with cetuximab plus irinotecan with combined corticosteroid and antihistamine premedication

Abstract: BACKGROUND:The multinational MABEL study of 1147 patients with metastatic colorectal cancer (mCRC) who had recently failed an irinotecan-containing regimen confirmed in a community practice setting the efficacy and safety of cetuximab combined with irinotecan. METHODS: This report describes a post hoc analysis of the influence of prophylactic premedication on the incidence of infusion-related reactions (IRRs) in the MABEL study. The analysis was focused on the subpopulation of patients premedicated with antihi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 34 publications
1
31
2
Order By: Relevance
“…Their results suggest the addition of dexamethasone, albuterol and famotidine to diphenhydramine prior to cetuximab reduces the incidence of overall as well as high-grade HSR. This finding is in agreement with a retrospective analysis of the MABEL trial, which indicated that dexamethasone as a premedication reduced the rate of HSR [2]. However, the data presented by Touma and colleagues demonstrate no clear beneficial effect of corticosteroids when added to diphenhydramine, with 22.6% and 12.9% of patients receiving the combination experiencing an HSR of any grade or high-grade, respectively.…”
supporting
confidence: 86%
“…Their results suggest the addition of dexamethasone, albuterol and famotidine to diphenhydramine prior to cetuximab reduces the incidence of overall as well as high-grade HSR. This finding is in agreement with a retrospective analysis of the MABEL trial, which indicated that dexamethasone as a premedication reduced the rate of HSR [2]. However, the data presented by Touma and colleagues demonstrate no clear beneficial effect of corticosteroids when added to diphenhydramine, with 22.6% and 12.9% of patients receiving the combination experiencing an HSR of any grade or high-grade, respectively.…”
supporting
confidence: 86%
“…It is very common, with up to 88% of patients experiencing a rash, but with most events being grade 1 and 2 [20]. Severe infusion reactions may occur in 1.4% to 4.5% [13,15,21], but it seems that they can be reduced by giving premedication with antihistamines and corticosteroids [22]. Hypomagnesaemia is a common side effect of CETUX that may occur in half of the patients receiving the treatment, with grade 3 and 4 events in as many as 25% of patients [23,24].…”
Section: Cetuximabmentioning
confidence: 94%
“…We recommend application of a potent topical corticosteroid to the sting site before the area is cooled with wet dressings or cool packs. The beneficial effects of antihistamines and/or systemic corticosteroids are well documented, for example for the prevention of late-phase drug reactions [15] and also of LLR during VIT [16]. Even if there are no controlled studies, it appears justified to recommend these drugs for the self-medication of LLRs.…”
Section: Management Of Large Local Reactionsmentioning
confidence: 98%